Psychological Features of the Relationship Between Hardiness and Anxiety - Mushcherova, Katerina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article describes the hardiness of the individual. It is represented by a set of attitudes, skills that provide courage, courage, bravery, and strategies that should turn stressors into opportunities for growth. Three main components are revealed: risk involvement, control and acceptance and their functions. It is determined that a person who has a high level of hardiness has a stable psychological and physical health, well adapted to the social space. It is noted that hardiness exists on three levels: psychophysiological (optimal responses to stress), socio-psychological (effective self-regulation) and personal-semantic (meaningfulness and positive worldview). Also, the essence of personality anxiety is characterized, it is presented as a certain emotional state of a person that arises under conditions of probable surprises in the case of postponement, delay of pleasant situations, and while waiting for trouble. It was found that anxiety can be both situational and personal. It is emphasized that situational anxiety arises from a stressful state or stimulus that affects a person at a particular time, and personal anxiety, in turn, is a personality trait that characterizes a person as prone to constant anxiety. Also identified and characterized are anxiety, neurotic, and moral anxiety. It is emphasized that anxiety can be a factor in mental problems, neuroses and fears. The article analyzes the results of an empirical study on the peculiarities of the manifestation of hardiness and anxiety of students. In particular, it was found that the average level of hardiness prevails among young people (45%) and the average level of anxiety, which tends to be high (33%). There is also a direct correlation between students’ resilience and anxiety. It was proved that the subjects who had a low level of hardiness had a high level of anxiety, and the subjects who, in turn, had a high and medium level of hardiness, had a low or medium level of anxiety, which tended to low.